Do evoked potentials matter? Pre-pathologic signal change and clinical outcomes with expandable cages in lateral lumbar interbody fusion surgery. (April 2022) - Malham, Gregory M.; Hamer, Ryan P.; Biddau, Dean T.; Munday, Nigel R.
Highlights: Evoked potentials in addition to EMG/tEMG is a more sensitive measure of "pre-pathologic" signal change, which was most often reversible. Patients that experienced intraoperative signal change in our study rarely correlated with a post-operative deficit. Our findings indicate that there is less clinical indication for routine neural monitoring at rostral lumbar levels. Abstract: Minimally Invasive Lateral Lumbar Interbody Fusion (MIS LLIF) is a reliable technique for treatment of degenerative disk disease, foraminal stenosis and spinal deformity. The retroperitoneal transpsoas approach risks lumbar plexus injury that may result in anterior thigh pain, sensory loss and weakness. A prospective study of 64 consecutive patients undergoing MIS LLIF with expandable cages (23 standalone, 41 integrated with lateral plate) using multimodal electrophysiological monitoring was performed. We measured sequential retraction times, complications, patient reported outcome scores and electrophysiologic findings with a minimum 12-month follow-up. Incidence of evoked potential and electromyographic signal change was moderate, and rarely resulted in post-operative neurologic deficit. Evoked potential signal changes were frequently resolved by the un-breaking of the surgical table or repositioning of the retractor. Average retraction times were 24 (15–41) minutes for standalone cages and 30 (15–41) minutes for integrated cages. At follow-up, the vast majority (97%) of patients reported significant clinical improvement post-operatively with only 2 patients reporting postoperative neurologic symptoms and subsequent recovery at 12-months. The present study shows that evoked potentials combined with electromyography is a more sensitive measure of pre-pathologic lumbar plexopathy in LLIF compared to electromyography alone, especially at L3/4 and L4/5 levels. Based on our findings, there is limited clinical indication for routine neural monitoring at rostral lumbar levels. The routine inclusion of multimodal electrophysiological monitoring in lateral transpsoas surgery is recommended to minimise the risk of neural injury by enabling optimal patient and retractor positioning and continued surveillance throughout the procedure.